2022
DOI: 10.3389/frma.2022.869974
|View full text |Cite
|
Sign up to set email alerts
|

Out-Look on Worldwide Trends of Related Studies on Citrus Waste as Feed for Livestock Production: A Scientometric Analysis

Abstract: The present study aimed to reveal the abundant tapestry of research on citrus waste and livestock feed, taking into account the recurring challenges posed by feed shortage and high price of conventional animal feed in livestock farming. In total, 565 articles were retrieved in a BibTeX format for analysis using bibliometric package in R studio. The retrieved data included, but not restricted to authors, citations, keywords, journals, and institutions. Published outputs on citrus waste and animal feed for lives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Other economically stable nations (e.g., Netherlands, United Kingdom, Australia, and China) also made up the numbers of the top institutions with high numbers of international co-authorships/networks. Similar findings from previous studies also showed that countries of a financially stable state have academic institutions associated with global networking and co-authorship in several other research niche areas (Zyoud, 2017;Idamokoro and Hosu, 2022c). Among the nations with leading co-authorships/networks are Kenya, Uganda, Tanzania, Zimbabwe, and South Africa, which is a somewhat rare scenario, but nevertheless a commendable one for these nations especially because of the high numbers of vulnerable (food insecure) people in these nations as compared to those in the developed countries.…”
Section: Discussionsupporting
confidence: 87%
“…Other economically stable nations (e.g., Netherlands, United Kingdom, Australia, and China) also made up the numbers of the top institutions with high numbers of international co-authorships/networks. Similar findings from previous studies also showed that countries of a financially stable state have academic institutions associated with global networking and co-authorship in several other research niche areas (Zyoud, 2017;Idamokoro and Hosu, 2022c). Among the nations with leading co-authorships/networks are Kenya, Uganda, Tanzania, Zimbabwe, and South Africa, which is a somewhat rare scenario, but nevertheless a commendable one for these nations especially because of the high numbers of vulnerable (food insecure) people in these nations as compared to those in the developed countries.…”
Section: Discussionsupporting
confidence: 87%
“…Solid citrus waste can be also utilized for the production of animal food. Due to its good nutritional composition containing dietary fibers, lipids, flavonoids, enzymes, vitamins, and carotenoids, citrus waste represents a promising by-product for the production of livestock feeds [ 105 ]. The literature reports that citrus pulp (the main residue after juice extraction), citrus molasses (produced by concentrating on the press liquor of citrus peel residue with a high content of sugars), citrus peel liquor (similar to molasses but not as concentrated), and citrus-activated sludge (produced from liquid waste) could be considered as by-product feedstuffs [ 106 ].…”
Section: Converting Waste Into Treasure—utilization Of Citrus By-prod...mentioning
confidence: 99%
“…There are numerous published overviews dealing with the valorization of citrus by-products and their potential utilization in the food and cosmetic industries, emphasizing also their health-promoting properties due to the presence of bioactive compounds [ 1 , 2 , 3 , 4 , 11 , 13 , 97 , 105 ]. The present study uses the recent available scientific literature linking citrus by-products to their potential biological, pharmacological, and biomedical applications and includes both the utilization of plant extracts and pure compounds that can be separated from the citrus by-products.…”
Section: Bioactivities Of the Individual Groups Of Compounds Present ...mentioning
confidence: 99%
“…To control insects, we seek a powerful substitute for synthetic chemical insecticides. In the past, natural compounds derived from plants were employed in animal diets for the beneficial effects of their antimicrobial flavoring agents in addition to some other nutritional impacts [ 1 ]. Several studies have discussed the effectiveness of natural-based plant products and or by-products, such as citrus peels in livestock, and other research has inspected active ingredients derived from their main sources using extraction methods, including flavonoids and polyphenols, because of their efficacy in their single-form rather than in the plant matrix [ 2 ].…”
Section: Introductionmentioning
confidence: 99%